2015
DOI: 10.1016/j.ajo.2015.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Limbal Basal Cell Density Decreases in Limbal Stem Cell Deficiency

Abstract: Purpose To investigate changes in limbal basal epithelial cell density in eyes with limbal stem cell deficiency (LSCD) using in vivo confocal laser scanning microscopy Design retrospective observational comparative study Methods A total of 43 eyes of 30 patients diagnosed with LSCD were included in the study. Ten eyes from normal subjects were included as control. Confocal imaging of the central cornea, and the superior, nasal, inferior and temporal limbus were collected using the Heidelberg Retina Tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 28 publications
2
36
0
3
Order By: Relevance
“…The clinical stages of LSCD could be divided into early, intermediate and late stages. Microstructural changes in the limbal area have a significant correlation with the clinical stage . Further investigation using high‐resolution imaging techniques is needed to evaluate the POV and limbal crypts in correlation to LSCD severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical stages of LSCD could be divided into early, intermediate and late stages. Microstructural changes in the limbal area have a significant correlation with the clinical stage . Further investigation using high‐resolution imaging techniques is needed to evaluate the POV and limbal crypts in correlation to LSCD severity.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo laser scanning confocal microscopy (LSCM), a non-invasive, real-time, three-dimensional technique that provides high-quality images of ocular surface tissues, has proved to be a promising tool in the diagnosis of LSCD. [4][5][6][7][8] LSCM is capable of not only defining the phenotype of the epithelium that covers the corneal surface but also visualizing the palisades of Vogt (POV), a widely accepted clinical marker to indicate the presence of LSCs. It has been confirmed that LSCM has a high degree of concordance with impression cytology in the diagnosis of LSCD.…”
Section: Introductionmentioning
confidence: 99%
“…13 Several reports have further demonstrated that the subbasal nerve plexus, corneal and limbal basal cell density and epithelial thickness correlate with the degree of LSCD. 16,17 These quantifiable parameters could be used to stage the degree of LSC function or deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…4, 911, 1316 The advantages of IVCM allow us to examine corneal nerve morphology and density in great detail. 10 The normal subbasal nerve plexus structure in healthy subjects has been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Significant microstructure changes have been reported in patients with LSCD and include a decrease in basal epithelial cell density (BCD), epithelial thickness and subbasal nerve density (SND), and stage-dependent morphologic changes. 11, 16, 17 Although previous studies report a reduction in SND or even absence of subbasal nerve plexus in severe LSCD, 11, 18 the study populations were small and detail characterization of the nerve morphology was not performed. The purposes of the present study are to further characterize the morphological changes of subbasal nerve plexus, quantify the changes of subbasal nerve in different stages of LSCD and investigate whether the SND decrease is correlated with the severity of LSCD in a larger study population.…”
Section: Introductionmentioning
confidence: 99%